2013
DOI: 10.1016/j.concog.2012.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary future projections are as frequent as involuntary memories, but more positive

Abstract: Mental time travel (MTT) is the ability to mentally project oneself into one's personal past or future, in terms of memories of past events or projections of possible future events. We investigated the frequency and valence of involuntary (spontaneously arising) MTT in the context of high trait worry. High (N=18) and low (N=16) worriers recorded the frequency and valence of involuntary memories and future projections using a structured notebook and completed measures probing individual differences related to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
84
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 54 publications
9
84
2
Order By: Relevance
“…Our results show that EmoFTs occur quite frequently in daily life, although there is substantial variation across individuals in this respect. This observation complements earlier investigations of future thinking in natural settings that did not specifically target the emotional component of prospection (Berntsen & Jacobsen, 2008;D'Argembeau et al, 2011;Finnbogadóttir & Berntsen, 2013;Klinger & Cox, 1987). For example, when examining any kind of future-oriented thoughts that might occur in daily life, D'Argembeau et al (2011) found that, on average, around sixty future-oriented thoughts were experienced each day and the content of about 60% of reported thoughts was judged to have an affective (either positive or negative) tone.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results show that EmoFTs occur quite frequently in daily life, although there is substantial variation across individuals in this respect. This observation complements earlier investigations of future thinking in natural settings that did not specifically target the emotional component of prospection (Berntsen & Jacobsen, 2008;D'Argembeau et al, 2011;Finnbogadóttir & Berntsen, 2013;Klinger & Cox, 1987). For example, when examining any kind of future-oriented thoughts that might occur in daily life, D'Argembeau et al (2011) found that, on average, around sixty future-oriented thoughts were experienced each day and the content of about 60% of reported thoughts was judged to have an affective (either positive or negative) tone.…”
Section: Discussionsupporting
confidence: 72%
“…On the other hand, little is known about the nature of emotional prospection occurring in natural settings. Results from diary studies have indicated that involuntary future event representations are as common as involuntary autobiographical memories in daily life, and that future event representations are more positive and idyllic than memories for past events (Berntsen & Jacobsen, 2008;Finnbogadóttir & Berntsen, 2013). In addition, positive future-oriented thoughts are more frequent (D'Argembeau et al, 2011), more specific, and associated with more visual images than negative future-oriented thoughts (Finnbogadóttir & Berntsen, 2011;D'Argembeau et al, 2011).…”
mentioning
confidence: 99%
“…However, evidence from naturalistic studies is mixed, with two recent experience-sampling studies reporting the prospective bias (Poerio, Totterdell, & Miles, 2013;Song & Wang, 2012) but an earlier study by Klinger and Cox (1987) failing to find any differences between the frequency of thoughts about the past and future. Moreover, in a diary study by Finnbogadóttir and Berntsen (2013) where participants recorded their involuntary thoughts about the past (i.e., memories) and the future during two separate 1-day periods, the number of recorded IAMs (M = 22.61) did not differ from the number of recorded future thoughts (M = 21.50) (see also Berntsen & Jacobsen, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, spontaneous remembering of past events without actively trying to remember anything has been termed Involuntary Autobiographical Memory (IAM) and studied as part of research on autobiographical memory with little overlap with research on mind-wandering (for exceptions see Finnbogadóttir & Berntsen, 2013;McVay & Kane, 2013;Song & Wang, 2012;Vannucci, Batool, Pelagatti, & Mazzoni, 2014). The aim of this paper is to take initial steps toward bringing together these two separate streams of research on mind-wandering and IAMs in the hope that this may provide interesting insights for both areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in a series of studies by Berntsen and colleagues (e.g., Berntsen, 1996;Berntsen & Jacobsen, 2008;Finnbogadottir & Berntsen, 2013), participants monitored the occurrence of involuntary (spontaneous) autobiographical memories and future thoughts in their daily life and recorded their characteristics in a diary. Overall, these studies have shown that involuntary autobiographical memories and future thoughts are common in daily life, are often activated in response to situational cues, and typically arise in states of diffuse attention.…”
Section: The Centrality Of Self-referential Thought When the Mind Wanmentioning
confidence: 99%